Sustainability and Sociological Change: Trends in Indonesian Islamic Architecture (Case Study at Islamic Village in Tangerang) - Suryandari, Putri; Kurniasih, Sri; Dyah, Anggraeni; Sen, Hasbi (JURNAL INDO-ISLAMIKA, 2024)
This research wants to know the sustainability and changes in the sociology of sharia housing in Indonesia, which has experienced a significant increase in the last five years and changes in Islamic housing architectural design post-occupancy. Does this also change the sociological system? This research aims to determine the sustainability of Islamic residential architectural design in the modern era. The research can be a reference for practitioners and the Muslim community in building Islamic housing. The research uses qualitative methods with a case study design. The location is the Islamic Village Housing Complex in Tangerang, Banten, with an area of 120 Ha. This research concludes that applying Islamic architectural design to modern Islamic housing is not sustainable as it is influenced by social, political, economic, and cultural changes due to globalization, modernization, and other contemporary challenges. Islamic housing sociology is sustainable in building solidarity between Muslim communities, maintaining religious traditions, and participating in social and economic development. Fair distribution of wealth and resources can reduce social disparities and fulfill human rights in sustainable development.